Tracheobronchial Foreign Bodies in Children: Experience From 1,328 Patients in China - Ling Ding; Ling Ding; Ling Ding; Ling Ding; Ling Ding; Shuping Su; Shuping Su; Shuping Su; Shuping Su; Shuping Su; Cheng Chen; Cheng Chen; et al. (Frontiers Media S.A., 2022)
Objective:To analyze the clinical characteristics of tracheobronchial foreign body (FB) cases in a pediatric Chinese population.MethodsThe clinical data of pediatric patients aged 0-18 years old diagnosed with a tracheobronchial FB in the Children's Hospital of Chongqing Medical University between September 2018 and August 2021 were analyzed retrospectively.ResultsAmong 1,328 included cases, 92.09% of patients were <3 years old, the male to female ratio was 1.86:1. The prevalence of tracheobronchial FB was similar between patients living in rural and urban areas and tracheobronchial FBs were more common in winter. The most common presenting symptoms were cough and wheezing. The most common CT findings was local obstruction or tracheobronchial narrowing, followed by obstructive emphysema of lung and pneumonia. The 11.3% of cases that did not report FB aspiration on admission had a longer time to hospital admission and longer hospitalization time than cases reporting FB aspiration (P < 0.05). The most common FB type was nuts (81.17%). FBs were more frequently located in the right bronchus, and 64 (4.82%) cases involved multiple FBs. FBs were expelled by coughing in only 4.07% of cases. For the other cases, FB removal by first bronchoscopy in our hospital was successful and complete in 96.86% of cases. 1.51% of patients had hypoxic ischemic encephalopathy (HIE) and the location of FBs was a possible risk factor for HIE (P < 0.05).ConclusionsTracheobronchial FBs occurred most commonly in children <3 years old. If asphyxia occurs in children which FBs aspirated, emergency treatment is needed to reduce the occurrence of HIE. Rigid bronchoscopy remains the first-line method for FB removal in children.